Our legal heritage A law-focused education program for young Americans - Berry, Russell I.; Hendrix, Marie H.; Heustess, W. Arthur (Alabama State Department of Education, 1983)
Gives the history of the United States system of law and discusses, through examples and case histories, the application of laws to daily life.